Blood saves lives: safe blood starts with me - Kipli, Nur Aida; Ramakrishnan, Prabha; Maniam, Yuthandy; Abdullah, Norazlin; Jack, Suriani; Abg Samah, Aizimah; Chiew, Fei Ha (Universiti Teknologi MARA, Sarawak, 2009)
With 318 pints of blood collections during 2007 blood donation campaign organized by Academic Bureau of KEKITA & Diploma in Nursing Program, UiTM Sarawak had won a Viagulam-Lazaramah Challenge Trophy for the new voluntary blood donors' recruitment campaign cum competition. This challenge trophy awarded to UiTM Sarawak in conjunction with 2008 Blood Donors Awards Presentation ceremony organized by The Malaysian Red Crescent Society, Kuching Chapter held in Auditorium Majlis Bandaraya Kuching Selatan on 19th July 2008. UiTM Sarawak was represented by Dr. Kamarudin Bin Jara'ee, UiTM Sarawak's Medical Officer to receive the trophy from Y.B. Dr. Abang Haji Abdul Rauf Abang Haji Zain on behalf of Y.A.B. Datuk Amar Puan Sri Dr. Hajjah Laila Taib, Patron of the Malaysian Red Crescent Society, Kuching Chapter. This trophy is a form of motivational award to encourage UiTM Sarawak to continuously involve and conduct such campaign in order to compete for the Cho Bok Challenge Trophy for Higher Learning Institutions /Schools.